(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
Youth empowerment through entrepreneurship is a strategic approach to strengthening rural economic independence and resilience. However, limited entrepreneurial capacity, restricted access to resources, and weak integration between local values and business ethics remain key challenges in rural areas. This community service program aimed to empower youth in Hoelea Village, Omesuri District, Lembata Regency, through entrepreneurship development integrating local wisdom and Maqasid Shariah values. The program employed a Participatory Action Research (PAR) approach involving 15 village youth aged 17–30 years through stages of problem and potential identification, participatory planning, entrepreneurship training, business mentoring, and participatory monitoring and evaluation. Data were collected through observation, interviews, focus group discussions, and questionnaires to assess changes in entrepreneurial understanding and motivation. The results indicate improved entrepreneurial readiness among participants, reflected in increased knowledge, motivation, and commitment to developing local potential–based enterprises. The program also facilitated the establishment of three youth business groups to strengthen local economic institutions, with one group successfully developing a local processed product called Kekis Lea made from moringa leaves. The integration of local wisdom and Maqasid Shariah values contributed to strengthening business ethics, social responsibility, and sustainability orientation. This program contributes to developing a participatory model of rural youth entrepreneurship that integrates local resources and ethical values, with continued support recommended to ensure sustainability and broader economic impact.